2020
DOI: 10.1007/s42865-020-00025-2
|View full text |Cite
|
Sign up to set email alerts
|

Forecast of precipitation for the 1994 flood in Piedmont: performance of an ensemble system at convection-permitting resolution

Abstract: The major flood that affected the Piedmont region in Italy in November 1994 is re-forecast after 25 years in ensemble mode at the convection-permitting resolution of 2.2 km using the regional model COSMO. The performance of the probabilistic forecast of precipitation is assessed against rain-gauge observations, also in comparison with the driver system, i.e., the probabilistic re-forecast produced by ECMWF based on the operational IFS (Cycle 46r1) at grid spacings of 18 km. The convection-allowing system dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The PIE1994 case was initially analysed by Buzzi et al (1998), who provided an exhaustive description of both the synoptic and small scale meteorological conditions that led to the disastrous flooding of a relatively vast area in northwestern Italy. Recently, several authors (Capecchi, 2020;Cerenzia et al, 2020;Davolio et al, 2020;Garbero and Milelli, 2020;Parodi et al, 2020) produced new reforecasts of the event by using state-of-the-art and limited-area numerical weather models (Meso-NH, COSMO, MOLOCH and WRF), all set in a convection-permitting mode. Although numerical experiments that shortly followed PIE1994 (Buzzi et al, 1998;Ferretti et al, 2000) were able to reproduce the rainfall due to the direct uplift of the flow impinging the Alps, it is by implementing higher-resolution and convection-permitting models that is possible to attain more accurate forecasts.…”
Section: Study Casesmentioning
confidence: 99%
“…The PIE1994 case was initially analysed by Buzzi et al (1998), who provided an exhaustive description of both the synoptic and small scale meteorological conditions that led to the disastrous flooding of a relatively vast area in northwestern Italy. Recently, several authors (Capecchi, 2020;Cerenzia et al, 2020;Davolio et al, 2020;Garbero and Milelli, 2020;Parodi et al, 2020) produced new reforecasts of the event by using state-of-the-art and limited-area numerical weather models (Meso-NH, COSMO, MOLOCH and WRF), all set in a convection-permitting mode. Although numerical experiments that shortly followed PIE1994 (Buzzi et al, 1998;Ferretti et al, 2000) were able to reproduce the rainfall due to the direct uplift of the flow impinging the Alps, it is by implementing higher-resolution and convection-permitting models that is possible to attain more accurate forecasts.…”
Section: Study Casesmentioning
confidence: 99%
“…The PIE1994 case was initially analysed by Buzzi et al (1998), who provided an exhaustive description of both the synoptic and small scale meteorological conditions that led to the disastrous flooding of a relatively vast area in northwestern Italy. Recently, several authors (Capecchi 2020;Cerenzia et al 2020;Davolio et al 2020;Garbero and Milelli 2020;Parodi et al 2020) produced new reforecasts of the event by using state-of-the-art and limited-area numerical weather models (Meso-NH, COSMO, MOLOCH and WRF), all set in a convection-permitting mode. Although numerical experiments that shortly followed PIE1994 (Buzzi et al 1998;Ferretti et al 2000) were able to reproduce the rainfall due to the direct uplift of the flow impinging the Alps, it is by implementing higher-resolution and convectionpermitting models that is possible to attain more accurate forecasts.…”
Section: Study Casesmentioning
confidence: 99%
“…These are: the finer grid spacing allowing for an enhanced physical and microphysical description of the processes, primarily due to not needing deep convection parametrization, the resulting higher level of topography detailing allowing for a better representation of atmosphere–land interactions, and the better adherence to assimilated regional observations. Previous studies reported multiple benefits related to increased grid resolutions in numerical simulations, allowing an adequate representation of local dynamical features and forcings leading to or intensifying precipitation events (Buzzi et al ., 2014; Cassola et al ., 2015; Clark et al ., 2016; Wahl et al ., 2017; Klasa et al ., 2018; Cerenzia et al ., 2020; Capecchi, 2021). Furthermore, the results obtained are in line with those of recently produced CP hindcasts over Italy, sharing similar characteristics with SPHERA, and obtained by downscaling ERA5 with the BOLAM/MOLOCH model (Capecchi et al ., 2022) or COSMO model (Raffa et al ., 2021; Reder et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%